(untitled) (African Journal of Biomedical Research, 2019)
The Modified Bass Technique (MBT) of tooth brushing is the most effective in plaque removal compared to some other reported techniques like Fones, Scrub, Charters and Stillman. We hypothesize that there will be a greater plaque reduction using the MBT as compared to the other reported techniques. The aim of this study therefore is to determine the effectiveness of the MBT compared to other tooth brushing techniques in plaque control. A 28 day clinical trial amongst 50 preclinical dental students was done. Participants were randomized into two groups, MBT group and other preferred tooth-brushing methods group. Data was collected using a self-administered semi-structured questionnaire on sociodemographic, oral health habits and knowledge on brushing techniques. The oral examinations were done by two calibrated examiners. Simplified Oral Hygiene Index (OHI-S), percentage plaque score and gingival bleeding score were recorded. The examiners and data analyst were blinded and data analysis was done using Paired T test with statistical significance of p< 0.05. Significant reduction was found in facial and interproximal plaque scores for both groups but more in the MBT group. There was significant reduction in gingival bleeding on probing in the MBT group after seven days while this was not significant in the other group (p>0.05). However, after 28 days, there was significant reduction in bleeding on probing in both groups. Within the limitations of this study, we found the Modified Bass Technique of tooth brushing to be more effective in plaque control compared to other brushing techniques.